A novel splicing mutation of ARHGAP29 is associated with nonsyndromic cleft lip with or without cleft palate. (3rd July 2022) - Yu, Qiuxia; Deng, Qiong; Fu, Fang; Li, Ru; Zhang, Wenwen; Wan, Junhui; Yang, Xin; Wang, Dan; Li, Fucheng; Wu, Shaoqing; Li, Jian; Li, Dongzhi; et al.
Abstract: Background: Nonsyndromic cleft lip with or without cleft palate (NSCL/P) is one of the most common birth defects, and occurs in approximately 1/700 live births worldwide. The correlation between the ABCA4-ARHGAP29 region and NSCL/P was first identified by genome-wide association studies (GWAS), but few reports have examined NSCL/P caused by ARHGAP29 mutations in the Chinese population. Methods: We performed chromosome microarray analysis (CMA) for two consecutive abnormal fetuses and whole exome sequencing (WES) for the family, including 3 patients and 2 normal family members, Sanger sequencing and RT-PCR were used to confirm the mutation. Results: We identified a novel splice donor mutation ( ARHGAP29 c.1920 + 1G > A) in two consecutive NSCL/P fetuses, and the variant was inherited from the mother and grandfather. The mutation caused abnormal skipping of exon 17, and the mRNA level of ARHGAP29 was significantly decreased compared to the wild type. Conclusions: In this study, we successfully diagnosed the genetic cause of NSCL/P in a family and first report that the c.1920 + 1G > A mutation in ARHGAP29 is associated with NSCL/P. Our study enriches the genetic landscape of NSCL/P, extends the mutation spectrum of ARHGAP29, and provides a new direction for the diagnosis of NSCL/P in patients and its prenatal diagnosis in fetuses.